2013
DOI: 10.1080/00207543.2013.842014
|View full text |Cite
|
Sign up to set email alerts
|

The incremental value of central control in serial supply chains

Abstract: We consider a two-echelon serial supply chain where a single manufacturer replenishes a single downstream customer who faces random, stationary and discrete demand. In this setting, we compare the performance of a traditional supply chain having no information sharing to one where the customer shares demand and inventory information with the manufacturer. We also consider the case of central control where the manufacturer has full control over replenishments. This full information sharing with control by the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 31 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…In the operations literature, it has been shown that the value of flexibility decreases as capacity utilization increases (Salzarulo & Jacobs, 2014). In the operations literature, it has been shown that the value of flexibility decreases as capacity utilization increases (Salzarulo & Jacobs, 2014).…”
Section: Physician Contracting Emphasis: Role Of Teaching Intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the operations literature, it has been shown that the value of flexibility decreases as capacity utilization increases (Salzarulo & Jacobs, 2014). In the operations literature, it has been shown that the value of flexibility decreases as capacity utilization increases (Salzarulo & Jacobs, 2014).…”
Section: Physician Contracting Emphasis: Role Of Teaching Intensitymentioning
confidence: 99%
“…As previously noted, one benefit of using contract physicians is the flexibility which they afford. In the operations literature, it has been shown that the value of flexibility decreases as capacity utilization increases (Salzarulo & Jacobs, 2014). High utilization levels blunt a manager's decision ability because the shortage of capacity limits their options for responding to variation or controlling the process.…”
Section: Physician Contracting Emphasis: Role Of Teaching Intensitymentioning
confidence: 99%
“…Analytical (Bakal & Akcali, 2006), (Hsiao & Shieh, 2006), (Ketzenberg et al, 2006), (Lin & Tsao, 2006), (Chiang & Feng, 2007), (Karaer & Lee, 2007), (Ganesh et al, 2008), (Ha & Tong, 2008), (Wu & Edwin Cheng, 2008), (Yao & Dresner, 2008), (Chen & Lee, 2009), (Liu et al, 2009), (Shang et al, 2010), (Bakal et al, 2011), (Jakšič, Fransoo, Tan, De Kok, & Rusjan, 2011), (Xue et al, 2011), (Axsäter & Viswanathan, 2012), (Chen, Liang, & Li, 2012), (Yang, Aydin, Babich, & Beil, 2012), (Cho & Lee, 2013), (Ganesh, Raghunathan, & Rajendran, 2014a), (Ganesh et al, 2014b), (Giloni, Hurvich, & Seshadri, 2014), (Lee & Cho, 2014), (Ruiz-Benítez et al, 2014), (Salzarulo & Jacobs, 2014), (Cannella et al, 2015), (Cui et al, 2015), (Kwak & Gavirneni, 2015), (Rached et al, 2015), (Wagner, 2015), (Babai et al, 2016), (Bian, Shang, & Zhang, 2016), (Bryan et al, 2016), (Sabitha, Rajendran, Kalpakam, & Ziegler, 2016), (Banerjee & Golhar, 2017), (Huang & Wang, 2017), (Li & Wang, 2017), (Lu et al, 2017), (Panagiotidou et al, 2017) Game theor...…”
Section: Type Of Decision Support Model Articlesmentioning
confidence: 99%
“…With regard to contract negotiation involving risk preferences, the literature falls into four categories: maximising utility function (Nagarajan and Sošić 2008;Sobel and Turcic 2008;Zhao et al 2010;Xie et al 2011;Hong et al 2013), using a mean-variance model (Lau and Lau 1999;Wei and Choi 2010;, under CVaR or VaR criterion (Yang et al 2009;Li, Lin, and Ye 2014) and others (Agrawal and Seshadri 2000;Yan 2004, 2005;Wang and Webster 2009;Giannoccaro and Pontrandolfo 2009;Salzarulo and Jacobs 2014). None of the literature considers the negotiation power in the process of contract negotiation.…”
Section: Literature Reviewmentioning
confidence: 97%